2006
DOI: 10.1212/01.wnl.0000201182.60750.66
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage design for a phase II clinical trial of coenzyme Q10 in ALS

Abstract: Several features of the Clinical Trial of High Dose Coenzyme Q10 in ALS study design promote efficiency. These features may be beneficial in phase II trials in amyotrophic lateral sclerosis and other fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…If there are several interventions or dosages of interest, and the objective is to decide which should be investigated further, a selection design can be employed [43]. The "best" agent or dosage to study is selected as the one that has the superior effect (e.g., has the highest group mean or highest percentage of positive responses); formal statistical comparisons are not performed.…”
Section: Designs For Late Exploratory Clinical Trial Designsmentioning
confidence: 99%
“…If there are several interventions or dosages of interest, and the objective is to decide which should be investigated further, a selection design can be employed [43]. The "best" agent or dosage to study is selected as the one that has the superior effect (e.g., has the highest group mean or highest percentage of positive responses); formal statistical comparisons are not performed.…”
Section: Designs For Late Exploratory Clinical Trial Designsmentioning
confidence: 99%
“…Likewise, very high doses of coenzyme Q10 are tried for the treatment of various other diseases such as Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis. The dosage under clinical trials is currently up to 3,000 mg/day for human use (Ferrante et al, 2005;Levy et al, 2006). For animal study, the dosage was up to 20,000 mg/kg/day as reported by previous researchers (Yang et al, 2005;Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II clinical trial, it was well tolerated and safe (Ferrante et al, 2005), but showed no efficacy in a phase II futility trial (NCT00243932) (Kaufmann et al, 2009;Levy et al, 2006).…”
Section: Coenzyme Q10mentioning
confidence: 99%
“…The symptoms of motor neuron disease (MND) have first been described by several neurologists by the mid-19 th century. The French neurologist Charcot defined the nosological entity "amyotrophic lateral sclerosis" (ALS) some years later (historic aspects of ALS are reviewed in (Eisen, 2007;Mitsumoto et al, 2006;Oliveira & Pereira, 2009;Rowland, 2001;Wijesekera & Leigh, 2009)). In the present understanding, MND comprehends a spectrum of different neurodegenerative syndromes which show a common neuropathology, i. e. the progressive degeneration of motor neurons.…”
Section: Introductionmentioning
confidence: 99%